2017
DOI: 10.1038/nchembio.2407
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of phosphorothioate DNA modifications leads to lethal genomic instability

Abstract: Genomic modification with sulfur as phosphorothioate (PT) is widespread among prokaryotes, including human pathogens. Apart from its physiological functions, the redox and nucleophilic properties of PT sulfur suggest effects on bacterial fitness in stressful environments. Here we show that PTs are dynamic and labile DNA modifications that cause genomic instability during oxidative stress. Using coupled isotopic labeling-mass spectrometry, we observed sulfur replacement in PTs at a rate of ~2%/h in unstressed E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 62 publications
(91 citation statements)
references
References 49 publications
1
89
0
1
Order By: Relevance
“…The prerequisite for these studies was the complete labeling of the nucleic acid with heavy, non‐radioactive isotopes such as carbon‐13, nitrogen‐15, and sulfur‐34 and access to a mass spectrometer. The combination of the different labeling media allowed the creation of a pulse‐chase experiment, which was used to observe repair of phosphorothioates in bacterial DNA . In the same year, we adapted the approach to RNA modification analysis in yeast .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…The prerequisite for these studies was the complete labeling of the nucleic acid with heavy, non‐radioactive isotopes such as carbon‐13, nitrogen‐15, and sulfur‐34 and access to a mass spectrometer. The combination of the different labeling media allowed the creation of a pulse‐chase experiment, which was used to observe repair of phosphorothioates in bacterial DNA . In the same year, we adapted the approach to RNA modification analysis in yeast .…”
Section: Introductionmentioning
confidence: 61%
“…NAIL‐MS overcame this limitation. The prerequisite for a discriminatory NAIL‐MS experiment was the availability of a heavy isotope‐labeling medium, which could label either the damaged or the natural product (e.g., here, methylation or thiolation). Feeding organisms with CD 3 ‐methionine led to the formation of CD 3 ‐SAM and transfer of heavy methyl marks onto the RNA (Figure S2) by the respective enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, in neutrophils, H 2 O 2 can be converted to the membrane permeable hypochlorous acid (HOCl) via myeloperoxidase 27 . HOCL can trigger oxidative unfolding of proteins 28 and is genotoxic to microbes 29 . Overall, through the production of these various reactive oxygen and nitrogen species, O 2 ·− lies at the heart of immune cell chemical warfare (Scheme 1).…”
Section: The Origins Of Superoxide In Biology and In Infectious Diseasementioning
confidence: 99%
“…). This result is understandable because bleomycin causes an increase in reactive oxygen species (Mahmutoglu et al ., ; Chen et al ., ), which react with PT to cause desulfurization and DNA breakage (Xie et al ., ; Kellner et al ., ). Taken together, our results revealed that DndB serves as an ATP sensor to regulate the transcription of the dndBCDE operon and the resulting PT modifications in an unusual autoregulated and reusable manner.…”
Section: Resultsmentioning
confidence: 97%
“…found that PT bonds are selectively sensitive to hypochlorous acid (HOCl), suggesting reduced bacterial fitness under commonly encountered oxidative stresses, e.g. in competition with organisms producing hypohalous acid (Kellner et al ., ). Tong et al .…”
Section: Introductionmentioning
confidence: 97%